Social Forestry in India - Tewari, D. N. (Indian Forester, 1991)
As per Nationa1 Forest Policy (1988) the national goal should be to have a minimum of one third of the total land area of the country under forests or tree cover. It is difficult to extend forest area but tree cover can increase substantially through social forestry programmes. Thus social forestry can increase the relative share of forest in the total land use pattern in the country. Social forestry must aim a need basis and time bound programme of afforestation and tree planting. It is imperative that social forestry should increasingly become a people's enterprise where the government has a supporting and non-implementing role. Social forestry being a People's Programme is different from traditiona1 forestry. It is necessary to strengthen the research activity in order to evolve new methodology in propogation of different plants needed by the people in their everyday life and also for generation of income. The productivity has to be increased per unit of area per unit time. The core message - "the tree is beneficial and essential for survival" must spread throughout the country. The social forestry extension worker must not only have a good knowledge of silviculture and social conditions in the working areas, but also be trained to work with people and to organise them for afforestation work. Land laws should be modified to facilitate individuals and institutions to undertake tree farming and grow fodder plants, grasses and legumes On their own land and degraded lands. Appropriate legislation should be undertaken to allow ownership and rights to harvest and sell their trees. West Bengal has shown a new approach in rehabilitation of degraded forest areas with the help of Forest Protection Committees. Several experiments are under trial for involvement of p.ople on sharing basis of the revenue from the growth of forest produce in different states. It is now recognised that agroforestry holds the potential for supplying a substantial part otcountry's Wood requirement. Driving force for agroforestry development must be the wood marketing (adequate and appropriate prices). Non-wood products provides sustenance to tribal and other communities. The importance of increasing production of such produce and their processing should be suitably incorporated.